Gluten-Free Breadmaking with Extruded Whole-Grain Andean Maize Flours - Miranda, Rita Marisol (2021)
Andean maize can be safely used in gluten-free bread formulation. Extrusion is a technology capable of promoting changes in the techno-functional properties of gluten-free flours, modifyingtheir breadmaking properties. The objective of this study was to evaluate the effect of extrusion onthe physical and physicochemical properties of Andean maize whole-grain flours (bolita race) and todetermine the relationship between the changes to the textural properties of gluten-free dough andbread with the addition of extruded flours. The Andean maize whole-grain flours were extruded in asingle-screw extruder. The moisture, temperature and screw speed were varied through an incomplete orthogonal design. The expansion degree of extruded products, the total soluble carbohydrates,and the gelatinization degree of the flours varied mainly with moisture and temperature extrusion.Flours with high, medium, and low degrees of gelatinization treatments were added at 20 % to nativeflours to make gluten-free dough and bread. The dough made with the addition of extruded floursincreased their firmness and adhesiveness in relation to the control made with native flour alone.Bread made with extruded flours generally increased their hardness, gumminess, chewiness, andcohesiveness. Springiness only increased under conditions of high and low degrees of gelatinization.The dough made with extruded flour at the extruded condition of 100 ◦C-25%H-120 rpm, withthe lowest degree of gelatinization, were the least firm and adhesive, which could lead to betterdough machinability. Additionally, the bread made with this flour presented high cohesiveness andspringiness.